Job satisfaction’s effects on fraud intentions on employees of financial companies in Semarang City - Rahayu, Puspita Puji; Anggraini, Melisa; Wulandari, Wulandari (International Journal Labs, 2024)
Today's business economic competition encourages companies to maximize the potential of human resources. Ideally, human resources have the capacity, capability, and integrity to maintain resilience in the business world, especially financial companies. However, the reality is that in Semarang City there are still fraud intentions in the form of corruption in employees of one of the banks, which has the potential to reduce company resilience. Job satisfaction is a reflection of workers' attitudes in responding to the work environment, this is related to the level of fraud intentions. This study aims to analyze the effect of job satisfaction on fraud intentions in employees of financial companies in Semarang City. The method used is quantitative-based with data collection techniques in the form of distributing questionnaires to 30 samples. The research data were tested using tests of validity, reliability, normality, linearity, and homoscedasticity. A simple linear regression analysis was performed for the impact of job satisfaction on fraud intensity. The results of this study show that there is a positive influence between job satisfaction and fraud intentions. The suggestion for future research is to extend the research period and take samples from all industries registered in Indonesia in various cities so that the research results can be used as generalizations.